2013
DOI: 10.1088/0031-8949/88/03/035801
|View full text |Cite
|
Sign up to set email alerts
|

Optical, mechanical and thermal characterization of l-threonine single crystals grown in dimethyl urea solution

Abstract: An organic material of a noncentrosymmetric l-threonine single crystal was grown in a dimethyl urea solution using the slow evaporation method. The grown crystal was transparent and colorless, with a size of about 20 × 7 × 4 mm3, obtained within a period of 10 days. The grown crystal was subjected to various studies, such as x-ray diffraction (XRD), Fourier transform infrared (FTIR), microhardness, ultraviolet–visible (UV–Vis) transmittance, thermogravimetric analysis and differential thermal analysis (TGA/DTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Rodriguez et al (2003) published a study of linear and nonlinear optical properties of this crystal, where they determined refractive indices and their dispersion, along with phase-matching conditions for second harmonic generation at a wavelength of 1064 nm (typical Nd:YAG laser wavelength for SHG experiments), proving the suitability of Lthreonine as nonlinear optical material. Recently, Shanti et al (2013) showed that from a solution of dimethylurea, large single crystals can be grown and confirmed the physical parameters published by Rodriguez et al (2003).…”
Section: Threoninesupporting
confidence: 58%
“…Rodriguez et al (2003) published a study of linear and nonlinear optical properties of this crystal, where they determined refractive indices and their dispersion, along with phase-matching conditions for second harmonic generation at a wavelength of 1064 nm (typical Nd:YAG laser wavelength for SHG experiments), proving the suitability of Lthreonine as nonlinear optical material. Recently, Shanti et al (2013) showed that from a solution of dimethylurea, large single crystals can be grown and confirmed the physical parameters published by Rodriguez et al (2003).…”
Section: Threoninesupporting
confidence: 58%
“…The key factor for successful growth of any crystal is the proper selection of solvents. To find out the suitable solvent, the solubility test was carried out by gravimetrical method [5] and here water was found to be the suitable solvent for growing crystals. The solubility of the solute can be determined by dissolving the solute in the solvent maintained at a constant temperature with continuous stirring.…”
Section: Growth and Solubilitymentioning
confidence: 99%